Flash photolysis of caged compounds in Limulus ventral photoreceptors (The Rockefeller University Press, 1992)
Rapid concentration jumps of Ins(1,4,5)P3 or ATP were made inside Limulus ventral photoreceptors by flash photolysis of the parent caged compounds. In intact ventral photoreceptors, the photolysis flash evokes a maximum amplitude light-activated current; therefore, a procedure was developed for uncoupling phototransduction by blocking two of the initial reactions in the cascade, rhodopsin excitation and G protein activation. Rhodopsin was inactivated by exposure to hydroxylamine and bright light. This procedure abolished the early receptor potential and reduced the quantum efficiency by 325 +/- 90- fold (mean +/- SD). G protein activation was blocked by injection of guanosine-5'-O-(2-thiodiphosphate) (GDP beta S). GDP beta S injection reduced the quantum efficiency by 1,881 +/- 1,153-fold (mean +/- SD). Together hydroxylamine exposure and GDP beta S injection reduced the quantum efficiency by 870,000 +/- 650,000-fold (mean +/- SD). After the combined treatment, photoreceptors produced quantum bumps to light that was approximately 10(6) times brighter than the intensity that produced quantum bumps before treatment. Experiments were performed with caged compounds injected into photoreceptors in which phototransduction was largely uncoupled. Photolysis of one compound, myo-inositol 1,4,5- triphosphate P4(5)-1-(2-nitrophenyl)ethyl ester (caged IP3), increased the voltage clamp current in response to the flashlamp by more than twofold without changing the latency of the response. The effect was not seen with photolysis of either adenosine-5'-triphosphate P3-1-(2- nitrophenyl)ethyl ester (caged ATP) or caged IP3 in cells preloaded with either heparin or (1,2-bis-(o-amino-phenoxy)ethane-N-N-N'-N' tetraacetic acid tetrapotassium salt (BAPTA). The results suggest that photoreleased IP3 releases calcium ions from intracellular stores and the resulting increase in [Ca2+]i enhances the amplification of the phototransduction cascade.